Case study: Including 3D printing in prosthetic fabrication for young children (Transactions on Additive Manufacturing Meets Medicine, 2025)
3D printing enhances pediatric prosthetics by improving customization, comfort, and adaptability. This study examines multi-year cases, highlighting the balance between additive and traditional craftsmanship. A hybrid approach ensures flexibility, optimizing fabrication for individual needs while maintaining clinical reliability.
Keywords: 3D printed prosthetics; paediatric prosthetics; case study